Pharmacokinetics of butorphanol following intravenous and intramuscular administration in donkeys: A preliminary study - Ebner, Lisa; O, Odette; Simon, Bradley; Lizarraga, Ignacio; Smith, Joe; Cox, Sherry (Frontiers in Veterinary Science, 2022)
The pharmacokinetics of butorphanol after intravenous (IVB) and intramuscular (IMB) administration in donkeys were determined in this preliminary study. Healthy male gelded donkeys (n = 5), aged 6 to 12 years old, were administered 0.1 mg/kg butorphanol IV or IM in a randomized, crossover design. Blood samples were obtained at predetermined intervals for 24 hours (IVB) and 48 hours (IMB) after administration. Plasma butorphanol concentrations were determined by high performance liquid chromatography and pharmacokinetic parameters were calculated. Following IVB administration, mean (± SE) apparent volume of distribution, elimination half-life, total body clearance, and area under the plasma concentration time curve from time 0 to infinity (AUC0–∞) were 322 ± 50 mL/kg, 0.83 ± 0.318 h, 400 ± 114 mL/hr/kg, 370 ± 131 h∙ng/mL, respectively. After IMB administration, a maximum plasma drug concentration of 369 ± 190 ng/mL was reached at 0.48 ± 0.09 hr. The IMB AUC0–∞ was 410 ± 60 h∙ng/mL. Bioavailability of IMB was 133 ± 45%. The pharmacokinetics of butorphanol in healthy donkeys was characterized by faster elimination half-life compared to values from the equine literature.